BVR POTSDAM AND HARVARD PHOTOMETRIES - MENDOZA, EUGENIO; GOMEZ, T (UNAM, Instituto de Astronomía, CD MEXICO, DF, MEX, 1970)
Multiple Regression Analysis has been used to find equations to transform Potsdam (Müller and Kempf, 1907) and Harvard (Pickering, 1908) visual photometries into the BVR photoelectric system (Johnson and Mitchell, 1962). The results indicate that the tran
BOL OBS TONAN TACUB
Keywords: BVR, POTSDAM, HARVARD, PHOTOMETRIES; ASTRONOMIA Y ASTROFISICA; COSMOLOGIA Y COSMOGONIA; ESTRELLAS